Isoliquiritigenin exerts antioxidant activity in Caenorhabditis elegans via insulin-like signaling pathway and SKN-1 - Link, Pille; Wink, Michael (Phytomedicine, 2019)
Background - Glycyrrhiza uralensis is a well-known medicinal plant. Different therapeutic effects have been reported for its secondary metabolites, including neuroprotective activity. Antioxidant properties have also been documented for some of its compounds and it could be a possible mechanism of neuroprotection. - Purpose - The present study was conducted to investigate the antioxidant effect and underlying pathways of G. uralensis and its main compounds. - Methods - The experiments were conducted with Caenorhabditis elegans, a simple in vivo model, widely used in this context. The methanol extract of G. uralensis and its main compounds isoliquiritigenin, liquiritigenin, glycyrrhizic acid, and glycyrrhetinic acid were tested for their effects on heat shock protein expression under mild oxidative stress and survival rate under lethal oxidative stress. To clarify the underlying pathways, the effect on the transcription factors DAF-16, SKN-1, and HSF-1 was tested. - Results - Isoliquiritigenin was the most potent compound in both assays, leading to a 31% decrease in expression of the stress marker heat shock protein and an 87% increase in survival rate. It significantly activated DAF-16 and SKN-1, but not HSF-1. - Conclusion - The present study identified isoliquiritigenin as the most active antioxidant compound in G. uralensis. It exerts its effect by activating the transcription factors DAF-16/FOXO and SKN-1/Nrf2 which regulate many genes, including those which code for proteins of antioxidative response. This implicates isoliquiritigenin as a possible supplement drug against oxidative stress especially in neurodegenerative diseases.
Available online 20 July 2018
Gesehen am 10.07.2019